Pemberdayaan Ekonomi Lokal melalui Sosialisasi UMKM Digital dan Diversifikasi Produk Lokal Singkong di Desa Cibatok 2 - Muhammad Akbar Zidane; Muhamad Ilham Zakaria; Radinda Swasti Maharani; Rahma Nur Aini Azzahra; Epa Malasari; Nabilla Azah Azzara; Hantrisa Nurrizki; Siti Puji Rahayu; I Gusti Putu Purnaba (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2026)
Cibatok 2 Village in Cibungbulang District, Bogor Regency, has significant agricultural potential in its abundant cassava commodity; however, its use is still limited to selling raw materials, resulting in suboptimal economic added value. Local UMKM also operate with simple business models, lack professional management, and make minimal use of digital technology for marketing, leading to low product competitiveness. The UMKM digitalization extension program and local product innovation workshop for cassava leaf jerky and ecoprint crafts by the KKN-T IPB group aimed to improve UMKM owners’ understanding of digitalization and the development of cassava by-products into high-value products. The implementation methods included an initial survey, digital UMKM socialization (computerization, digitalization, e-commerce, and digital marketing), local product innovation workshops, and evaluation involving active community and UMKM groups (PEKKA) participation. Pre-test and post-test results showed a significant improvement in participants’ knowledge, with the average score increasing from 2.435 to 3.080. The program enhanced participants’ understanding of digital UMKM and the importance of local product innovation for business sustainability, resulting in innovative products such as cassava leaf jerky and cassava leaf-patterned bags using the ecoprint technique. Participants’ enthusiasm and positive feedback are expected to motivate the development of local products combined with digital marketing, thereby increasing product value, expanding market reach, and encouraging local economic growthowner. Proficiency in digital technology and creative processing of local potential can be effective strategies to strengthen the village economy; therefore, further training, continuous mentoring, and strengthened marketing strategies are recommended to ensure the sustainability of the program.